2019
DOI: 10.1038/s41391-019-0131-8
|View full text |Cite
|
Sign up to set email alerts
|

Total nut, tree nut, peanut, and peanut butter intake and the risk of prostate cancer in the Netherlands Cohort Study

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…As expected, recent epidemiological studies identified an inverse correlation between frequent nut consumption and the risks of cancer incidence [4] and mortality [8]. However, other studies observed no significant association [11,12]. Therefore, these conclusions require further investigation.…”
Section: Introductionmentioning
confidence: 69%
“…As expected, recent epidemiological studies identified an inverse correlation between frequent nut consumption and the risks of cancer incidence [4] and mortality [8]. However, other studies observed no significant association [11,12]. Therefore, these conclusions require further investigation.…”
Section: Introductionmentioning
confidence: 69%
“…The Netherlands Cohort Study (2019) on 58,279 men aged 55–69 years exhibited no remarkable correlation between the consumption of peanuts, other tree nuts, and total nuts and advanced, nonadvanced, and total PCa. However, consumption of peanut butter was observed to have a direct relationship with the risk of nonadvanced PCa 29 …”
Section: Resultsmentioning
confidence: 94%
“…The null nut consumption-overall prostate cancer association reported here is largely consistent with previous prospective cohort data, i.e., the Adventist Health Study, with men followed for up to only six years, showed no association between current consumption of nuts and prostate cancer risk [6], the Health Professionals Follow-up Study also concluded that there was no association between nut consumption and prostate cancer incidence (HR = 0.98, 95% CI = 0.89-1.09, P-trend = 0.61), although a possible association with frequency of consumption was indicated [5], and the Netherlands Cohort Study also reported no nut consumption-prostate cancer risk association (HR = 1.09, 95% CI = 0.92-1.29, P-trend = 0.41) [7]. Furthermore, a recent dose-response meta-analysis (n = 6 studies) found no statistically significant association between total nut intake and risk of prostate cancer; suggesting a limited number of studies available for analysis, and highlighting the importance of additional prospective large cohort studies to re-examine these associations [8].…”
mentioning
confidence: 94%
“…The nutrients in nuts may modify specific processes related to cancer development such as regulation of cell differentiation and proliferation, reduction of tumor initiation/promotion and DNA damage, and regulation of immunologic inflammatory responses [3]. In vitro data also suggests that antioxidant micronutrients protect biomolecules that can influence cancer risk [3,4].Prospective analyses in the Health Professionals Followup Study, Adventist Health Study, and the Netherlands Cohort, as well as a systematic review, examined total consumption of nuts and peanut butters and reported no association with prostate cancer risk [5][6][7][8]. However, two case-control studies showed inverse nut consumptionprostate cancer associations [9,10].…”
mentioning
confidence: 99%
See 1 more Smart Citation